Kontruksi Pemikiran Rosdalina Bukido terhadap Penegakan Hukum di Indonesia: Analisis Sociological Jurisprudence untuk Mewujudkan Keadilan dan Efektivitas - Nasriah, Nasriah; Sugitanata, Arif; Hasan, Faradila (Lisyabab : Jurnal Studi Islam dan Sosial, 2024)
This research delves deeply into the issue of law enforcement in Indonesia, focusing on the contribution of Rosdalina Bukido's thoughts. This research utilizes a qualitative research method based on literature studies by analyzing Rosdalina Bukido's works related to efforts to maximize law enforcement in Indonesia and applying Roscoe Pound's Sociological Jurisprudence theory. The results highlight the urgency of effective and just law enforcement in nation-building. Bukido emphasizes the role of judges as justice carriers, detailing the gap between theoretical law and daily practices. Internal and external factors influencing law enforcement are discussed, emphasizing consistency in legal principles, professionalism of law enforcers, and public perception of the law. Analysis of Bukido's ideas from the Sociological Jurisprudence perspective highlights the dynamic relationship between law and society. Her contributions include deep understanding of how law must be responsive to its social context and fulfill societal needs and aspirations. Hence, there are important contributions in Rosdalina Bukido's thinking in understanding and implementing law enforcement in Indonesia. The application of Sociological Jurisprudence provides a broader view of how law operates within society. The implications include the necessity of consistency in legal principles, professionalism of law enforcers, and changes in public perception to create a more just and effective legal system.